The Role of Adhocratic Leadership in Facing the Changing Business Environment - Karneli, Okta (PT. LITERASI SAINS NUSANTARA, 2023)
Changes in today's business environment are increasingly complex and cannot be predicted with certainty. Factors such as technological developments, market dynamics, and regulatory changes are challenges that organisations and companies must face. In the face of these rapid changes, adaptive and flexible leadership becomes critical to ensure business success and continuity. This research aims to analyse the role of adhocratic leadership in dealing with the changing business environment. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that adhocratic leadership plays an important role in dealing with rapid and dynamic changes in the business environment. This leadership approach emphasises flexibility, innovation, rapid adaptation, and collaboration to respond to changing market and customer needs. Adhocracy leaders must be risk-takers, make smart use of technology and data, and create an organisational culture that supports innovation and continuous learning.